Detection of Canonical Hedgehog Signaling in Breast Cancer by 131-Iodine-Labeled Derivatives of the Sonic Hedgehog Protein. (28th June 2012) - Sims-Mourtada, Jennifer; Yang, David; Tworowska, Izabela; Larson, Richard; Smith, Daniel; Tsao, Ning; Opdenaker, Lynn; Mourtada, Firas; Woodward, Wendy
Abstract : Activation of hedgehog (HH) pathway signaling is observed in many tumors. Due to a feedback loop, the HH receptor Patched (PTCH-1) is overexpressed in tumors with activated HH signaling. Therefore, we sought to radiolabel the PTCH-1 ligand sonic (SHH) for detection of cancer cells with canonical HH activity. Receptor binding of 131 I-SHH was increased in cell lines with high HH pathway activation. Our findings also show that PTCH-1 receptor expression is decreased upon treatment with HH signaling inhibitors, and receptor binding of 131 I-SHH is significantly decreased following treatment with cyclopamine. In vivo imaging and biodistribution studies revealed significant accumulation of 131 I-SHH within tumor tissue as compared to normal organs. Tumor-to-muscle ratios were approximately 8 : 1 at 5 hours, while tumor to blood and tumor to bone were 2 : 1 and 5 : 1, respectively. Significant uptake was also observed in liver and gastrointestinal tissue. These studies show that 131 I-SHH is capable of in vivo detection of breast tumors with high HH signaling. We further demonstrate that the hedgehog receptor PTCH-1 is downregulated upon treatment with hedgehog inhibitors. Our data suggests that radiolabeled SHH derivatives may provide a method to determine response to SHH-targeted therapies.